Lattices in a product of trees, hierarchically hyperbolic groups and virtual torsion‐freeness. Issue 4 (6th April 2022) - Hughes, Sam
Abstract: We construct cocompact lattices in a product of trees which are not virtually torsion‐free. This gives the first examples of hierarchically hyperbolic groups which are not virtually torsion‐free.